Poverty and poverty alleviation programmes in the Sudan: Policy and administration - Eissa, Garoot Suleiman (s.n, 2013)
Sudan is among those developing countries characterized by high incidence of poverty in spite of its prodigious resource endowments. Sudan government has continued to introduce programmers aimed at alleviation of poverty which were generally characterized by lack of effectiveness. The traditional approach towards poverty reduction centered on national development programmer designed to enhance economic growth and improve standard of living. The paper reviews the history of micro-credit and micro-finance in the country